Study of Groin Structure Planning On a River Bend In Padang Mancang Village - Muhammad Arrie Rafshanjani amin; SAFRIANI, MEYLIS; Cut Suciatinas Silvia; Delfian Masrura; Safrizal (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2025)
The river flows naturally from its source (upstream) to its mouth (downstream). Due to its velocity, riverbank erosion often occurs, especially in curved sections. In meandering rivers, unstable soil can lead to landslides on the outer banks. One affected area is Padang Mancang Village, Kaway XVI Subdistrict, West Aceh Regency. This study aims to design a suitable groin structure to mitigate erosion. The design process considers a 50-year return period flood (Q50), soil properties, and river cross-section data. The proposed groin structure has a length of 30 meters, a foundation width of 10 meters, a top width of 3 meters, and a height of 12 meters. The flood discharge is 2885.307 m³/s. Stability analysis confirms the structure is safe, with safety factors of 3.06 for overturning and 1.89 for sliding, both exceeding the minimum 1.5. The foundation is stable, with a maximum stress of 2.076 kg/cm², below the allowable 7.71675 kg/cm². These results indicate the groin structure effectively prevents riverbank erosion while ensuring structural stability.